Novel method of preparing hierarchical porous CoFe2O4 by the citric acid-assisted sol-gel auto-combustion for supercapacitors. (March 2021) - Huang, Tianfu; Qiu, Zehai; Hu, Zhibiao; Lu, Xiaochun
Highlights: The hierarchical porous CoFe2 O4 was fabricated by the new novel sol-gel auto-combustion method. Process and mechanism of CoFe2 O4 formation was system analyzed. The capacitive performance of CoFe2 O4 was significantly improved. Possible mechanism for the enhanced capacitive performance was proposed. Abstract: In this work, the hierarchical porous CoFe2 O4 was fabricated by the citric acid-assisted sol-gel auto-combustion method. The hierarchical porous CoFe2 O4 was applied as supercapacitor's electrode and exhibited good electrochemical properties. The specific capacitance of CoFe2 O4 electrode can rich 443.89 F g −1 at current density of 1 A g −1, and 75.12% capacitance was still retained at current density of 16 A g −1 compared with 1 A g −1 . The cycling stability was excellent, which degraded by 20.65% after 6000 cycles. The results suggest that the synthesized hierarchical porous CoFe2 O4 was a promising candidate for application to supercapacitors electrodes. Meanwhile, the novel citric acid-assisted sol-gel auto-combustion is low manufacturing cost, simple in preparation, easy to control the stoichiometric ratio, which can be further extended to synthesize other inorganic materials.